Penerapan Pemidanaan Terhadap Anak Sebagai Pelaku Tindak Pidana Pembunuhan Berdasarkan Prinsip Perlindungan Anak (Jurnal Begawan Hukum (JBH), 2024)
The legal principle states "nullum crimen sine poena legal", which means there is no criminal act without a crime according to the law. In principle, this principle means that no crime can be punished if it is not prohibited by law, so that actions and crimes must first be regulated by law. Likewise with this crime of murder. Where the crime of murder is a crime that violates very serious norms. The crime of murder is not only committed by adults, but children can also be involved in this crime.The crime of murder is a crime that can occur because it is carried out intentionally or because of someone's negligence/negligence, resulting in victims or the loss of another person's life.Handling of children involved in crime, especially children who are perpetrators of murder, must be given serious attention. Not only for the government but also for law enforcement officers and other parties including the surrounding environment. This treatment is quite important because the perpetrators who are categorized are still children. Handling cases in children cannot be the same as handling cases in adults, so there are many things that must be paid attention to and taken into consideration. One of them is the juvenile justice system.